Graphene as a heat transfer enhancer for ternary molten salt applications - Li, Li; Noor, M. M.; Syam, M. M.; Gajghate, Sameer S.; Kadirgama, Kumaran; Lu, Hongkun (Nature Research, 2026)
In this work, it is shown how a reliable nitrate based composite phase change material (PCM) of low melting point and extended operating temperature range can be formulated, to be used in applications for medium-low temperature thermal energy storage. A eutectic ternary nitrate system of (NaNO3-KNO3-LiNO3) has been used as the phase change matrix, to which nanoparticulate graphene has been used as a functionalized additive material. The thermophysical characterization and morphological tests show that the doping of graphene can effectively manipulate the thermal properties and micro morphology of the ternary nitrate composite. It is shown that the addition of graphene results in a significant increase in the initial decomposition temperature compared to the neat salt system. Of the composite systems made, the one with 1.0 wt% of graphene loading gave the highest initial decomposition temperature, maximum melting temperature (Tm), peak enthalpy (ΔH) of phase transition. Microscopic studies have shown that a graphene loading of 0.5 wt% gives the most uniform grain distribution within the composite. The results presented here give a conceptual basis for the use of composite ternary nitrate/graphene systems in concentrating solar power (CSP) energy systems. Demonstrated are the results obtained which show the potential of these materials for efficient thermal energy storage in renewable power technologies. This study describes the preparation of a low melting point and thermally stable nitrate composite phase change material (PCM) usable for medium-low temperature thermal energy stores. The eutectic ternary nitrate system based on NaNO3-KNO3-LiNO3 having the finely adjusted composition of 12:53:35 by weight building upon the well-known Solar Salt and Hitec salt, was employed as the phase change matrix while the functional additive was graphene nanosheets. Thermophysical characterisation showed that the inclusion of graphene enhanced the thermal properties of the matrix substantially: the composite containing 1.0 wt% of graphene showed an increase in phase change enthalpy of 30.2% as compared to the pure ternary nitrate (from 4.00 J/g to 5.21 J/g), There was an increase of the initial decomposition temperature (from 597 °C to 617 °C) and a decrease of the melting temperature (from 97.6 °C to 76.6 °C) of 21.5%. The microstructural analysis showed that the addition of 0.5 wt% graphene favoured the most uniform grain distribution in the matrix. These results provide technical support for the use of ternary nitrate/graphene composites in CSP systems.